2019
DOI: 10.1109/access.2019.2923358
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Free Control Method for Synchronous Vibration of Active Magnetic Bearing Rotor System

Abstract: The unbalanced force on the active magnetic bearing (AMB) rotor system is the main reason of system vibrations, which always have periodic repetitive characteristics. However, the closed-loop feedback control system (CFCS) is difficult to achieve effective control of these repetitive problems. In this paper, we firstly analyzed the synchronous vibration by taking AMB rotor mass imbalance as an example. Then, we proposed a model-free control (MFC) method based on the Newton-type ILC algorithm, and the key of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Most research results on the AMB rotor unbalance control need to extract the periodic components of the signal, but unfortunately most of them only described the algorithm theory and did not analyze the existing problems from the perspective of digital control system. [11][12][13][14][15][16][17][18][19][20][21] However, we found PCEA based on Fourier transform theory would occupy numerous computing resources, which ultimately cannot meet the real-time requirement of the control system.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research results on the AMB rotor unbalance control need to extract the periodic components of the signal, but unfortunately most of them only described the algorithm theory and did not analyze the existing problems from the perspective of digital control system. [11][12][13][14][15][16][17][18][19][20][21] However, we found PCEA based on Fourier transform theory would occupy numerous computing resources, which ultimately cannot meet the real-time requirement of the control system.…”
Section: Problem Formulationmentioning
confidence: 99%
“…By comparing equations (21) and (24), it can be concluded that under the completely identical conditions that include the parameters and the initial state of the system, the convergence rate based on ILC-1 is faster than ILC-2.…”
Section: Evaluation Of Convergence Rate Based On Spectral Radiusmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-free control based on a data-driven control method has been widely studied [17] [18]. This approach constructs the controller using input and output data of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…In the above article [1,, an experimental condition is missed. The detailed experimental conditions are described as:…”
mentioning
confidence: 99%